Exploring Digital Marketing Practices for KUNTUM Magazine Publishing Company in Malaysia (Journal of Entrepreneurship and Business, 2021)
The development of new media has made a significant impact on all areas included in the business sector. Many marketers use new media platforms through websites and social media now become a phenomenon and important to the business world landscape. Digital marketing is one form of marketing commonly used for promoting goods or services and reaching customers across digital channels. The aspects of digital marketing conducted through websites and social media platforms can be used by magazine publishing companies to ensure enhanced product marketing activities. The goal of this study was to analyze the degree to which magazine publishers such as Kuntum magazine used their website and social media sites as their digital marketing strategies and explore the understanding of the definition and role of the digital marketing dimension by the publishing company and its effectiveness as a modern marketing tool. This research interviewed the Editor and Kuntum magazine employees using qualitative approaches. The findings show that with the change in their digital marketing strategy, Kuntum magazine is increasingly utilizing new media channels, and very optimistic. This research looks forward to finding a more effective and sustainable approach in the transition of the magazine publishing industry to digital marketing practices.
Keywords: Array; Array; Array; Array